Manajemen Sarana dan Prasarana di SMP Negeri 255 Jakarta - Angga Harizki; Wahyu Sri Ambar Arum; Neti Karnati (Universitas Negeri Jakarta, 2017)
The research aimed to identify and obtain an overview of the maintenance and inventory of educational facilities. This research was conducted in in SMP Negeri 255 on May 2015 through June 2016. The research used a qualitative approach with descriptive methods. Data was collected through interviews, observation and documentation. Source data from this study came from key informants that the vice principal fields of infrastructure, while supporting informant I is treasurer of goods and informants II is the principal. Results from the study showed that (1) Mechanical maintenance of educational facilities that do SMP Negeri 255 Jakarta include awareness, understanding, organizing, implementation and data collection. Problems that occur in the technical maintenance of educational facilities is the lack of a clear division of labor, funding needs due to late disbursement of BOS and BOP, and difficulty to obtain experts. (2) Procedures inventory of educational facilities was conducted on the recording, coding and inventory evaluation. Problems that occur in the inventory procedure for school infrastructure is often the goods delivered are not in accordance with the required specifications of the school, so that has caused delays in the process of recording goods.